ANALYSIS OF THE PROCESS OF DEEP MACHINE LEARNING BASED ON THE RESULTS OBTAINED FOR PRIMARY DIAGNOSTICS OF GASTROENTEROLOGICAL DISEASES - Rustam Yaxshiboyev; Bahodir Muminov; Erkin Ermetov; Abdunazar Jurayev (Central Asian Journal of Medicine, 2023)
This article discusses the analysis of the process of deep machine learning based on the results obtained for the primary diagnosis of gastroenterological diseases. The process of deep machine learning was carried out, the ANN and SVM algorithms were used. The results of deep machine learning were compared, two variants of data sets for training were collected. Based on deep machine learning, it is planned to further develop a software and hardware complex for the primary diagnosis of gastroenterological diseases.